2010
DOI: 10.2459/jcm.0b013e328332e926
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of catheter ablation versus antiarrhythmic drugs for atrial fibrillation: a meta-analysis of randomized trials

Abstract: In selected patients with atrial fibrillation, RFCA is a relatively effective and well-tolerated procedure to cure atrial fibrillation. Even though the results of our systematic review favour ablation therapy, large, well-designed RCTs are needed to confirm the efficacy and safety of RFCA for the management of atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…A meta-analysis of 8 randomized trials with total of 844 patients confirmed safety of catheter ablation. Fewer adverse effects were registered among patients treated with AF ablation than in those treated with AADs (RR 0.72 [95% CI: 0.40 to 1.30]; p=0.28) [102].…”
Section: Figure 3 Catheter Ablation Of Persistent Af: Pv Isolation Amentioning
confidence: 99%
“…A meta-analysis of 8 randomized trials with total of 844 patients confirmed safety of catheter ablation. Fewer adverse effects were registered among patients treated with AF ablation than in those treated with AADs (RR 0.72 [95% CI: 0.40 to 1.30]; p=0.28) [102].…”
Section: Figure 3 Catheter Ablation Of Persistent Af: Pv Isolation Amentioning
confidence: 99%
“…Prior to the present study, a number of previous meta-analyses were published that compared catheter ablation with AADs for the treatment of AF (29)(30)(31). However, the present study possesses a number of advantages compared with the previous studies.…”
mentioning
confidence: 48%
“…In selected patients, the Cox maze procedures achieve >80% freedom from atrial fibrillation at 1-year follow-up [66]. Catheter-based ablation of atrial fibrillation is less invasive and seems to reduce recurrence of atrial fibrillation in selected patients by~70% [67,68]. However, these attempts to eliminate the rhythm still have significant atrial fibrillation recurrence at approximately 25% in controlled trials and should not be an approach to avoid anticoagulation.…”
Section: Atrial Fibrillationmentioning
confidence: 99%